Do senior citizens prefer dividends? Local clienteles vs. firm characteristics - Krieger, Kevin; Lee, Bong-Soo; Mauck, Nathan (Journal of Corporate Finance, 2013)
We examine the payout policy of U.S. firms over the period 1980–2008. Prior research indicates that firm characteristics, managerial preferences, and investor clienteles are all important factors in setting payout policy. Counter to the oft-reported positive relation between senior citizens and the use of dividends, we find no such significant relation. Our results indicate that either senior citizens are indifferent between dividends and repurchases, or that if seniors do demand dividends, they have no influence over firm payout policy. The evolution of firm characteristics, including the average firm size, age, and volatility of earnings over time, best explains payout policy.